Die präoperative Anwendung von Dutasterid hat keine Auswirkung auf intraoperative Blutungen bei transvesikaler offener einfacher Prostatektomie zur Behandlung der benignen Prostatahyperplasie - Guner, Ekrem; Ugur, Ramazan (Aktuelle Urologie, 2020)
Objective There are a few studies in the literature investigating the effect of preoperative dutasteride use on bleeding in open simple prostatectomy. We aimed to evaluate the effect of preoperative dutasteride use on perioperative bleeding during open simple prostatectomy.Methods We retrospectively analyzed the medical records of all patients who underwent transvesical open prostatectomy due to benign prostatic hyperplasia in our institution between 2008 and 2018. Patients were divided into 2 groups regarding the use of dutasteride prior to surgery as group 1 = received dutasteride during at least six weeks prior to surgery; group 2 = dutasteride naive.Results: A total of 167 patients who met the inclusion criteria were included in the study. The mean operative time was 86.5±18.7 min while the estimated blood loss was 640.7±55.7 ml. There was no statistically significant difference in operative time, estimated blood loss, hemoglobin, and hematocrit decrease among the two groups.Conclusion We were not able to find an advantage of pre-operative dutasteride use in terms of perioperative bleeding in open simple prostatectomy performed for benign prostatic hyperplasia.
Keywords: benign prostatic hyperplasia; bleeding; dutasteride; open simple prostatectomy; 5α-reductase inhibitors